Degree of hydration of OPC and OPC/FA paste samples - Shafiq, N.; Nuruddin, F (2010)
Degree of hydration of cement paste controls many properties of hardened concrete and/or mortar such as compressive strength. During the drying process, the degree and the rate of hydration of cement paste in concrete/mortar samples are significantly affected by the ambient relative humidity of the exposure conditions. There are various parameters such as the amount of calcium hydroxide, Ca(OH)2 in the paste, quantity of the chemically bound water, specific gravity of the paste, fraction of un-hydrated cement, liberated heat of hydration and strength of the hydrated cement may be used to determine the degree of hydration of the cement paste. This paper presents the results of the experimental investigation for the determination of the degree of hydration of 100% cement paste and fly ash blended cement pastes. After 28 days moist curing, the samples were conditioned in 100%, 75%, 65%, 40% and 12% relative humidity. Conditioning of samples in different relative humidity had significant effects on the compressive strength of the mortar samples and the degree of hydration of the paste samples. Conditioning of samples in 100% RH resulted in higher compressive strength and the degree of hydration. Because of the 28 days moist curing and 12 weeks moisture conditioning in different RH, fly ash based samples showed better compressive strength than the OPC samples.